hsa_circ_0008305 facilitates the malignant progression of hepatocellular carcinoma by regulating AKR1C3 expression and sponging miR-379-5p - Shenglan Huang; Kan Liu; Yongkan Xu; Hua Wang; Shumin Fu; Jianbing Wu (Scientific Reports)
Abstract Circular RNAs (circRNAs) are widely involved in diverse biological processes of cancers. Nonetheless, the potential function of hsa_circ_0008305 in hepatocellular carcinoma (HCC) remains largely unknown. This study aims to elucidate the role and underlying mechanism of hsa_circ_0008305 in HCC. Our findings reveal that the novel circRNA hsa_circ_0008305 (circPTK2) is significantly upregulated in HCC tissues, with its elevated expression being positively correlated with advanced tumor T stage and vascular invasion. The circular characteristics and subcellular localization of hsa_circ_0008305 was determined by RNase R treatment and RNA nucleocytoplasmic separation. Further functional assays, including CCK8, EdU, colony formation assays, scratch-healing, transwell assays, and Xenograft tumor models were conducted to explore the biological functions of circPTK2. The regulatory mechanisms of circPTK2 were elucidated through RNA sequencing, enrichment analysis, and dual luciferase reporter assay. Our findings indicate that circPTK2 is stably localized in the cytoplasm. Functionally, circPKT2 promoted the HCC cells proliferation, migration, and invasion both in vitro and vivo. Mechanistically, circPTK2 was found to positively regulates the expression of AKR1C3 by acting as a sponge for miR-379-5p. Inhibition of miR-379-5p significantly mitigates the biological effects induced by circPTK2. AKR1C3 is identified as a direct target of miR-379-5p, and silencing AKR1C3 overturns the promotion progression effects of miR-379-5p inhibitor. In conclusion, our results revealed that circPTK2 facilitates the malignant progression of HCC via sponging miR-379-5p to up-regulate AKR1C3 expression.